PENGELOLAHAN SAMPAH ORGANIK MENJADI CHERRY LEAF GUMMY YANG MEMPUNYAI NILAI JUAL DALAM MENINGKATKAN EKONOMI KELUARGA DI KABUPATEN SITUBONDO - Hasanah, Nur; Romlah, Romlah; Safitri, Emilia (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
This community service activity was carried out to provide training to the community in processing organic waste into Cherry Leaf Gummy which has a selling value in improving the family economy in Situbondo Regency. This organic waste management is one of the strategic solutions in reducing the volume of waste while increasing the economic value of previously unused materials. This community service activity aims to empower the community in Situbondo Regency through innovation in processing organic waste, especially cherry leaves, into processed food products in the form of Cherry Leaf Gummy which have a selling value. The methods used include socialization, direct training, and technical assistance to target community groups. The results of the activity show that the community is able to process cherry leaves into gummy products that are liked by consumers because of their unique taste and health benefits. In addition to reducing organic waste, this product also provides new business opportunities that contribute to improving the family economy. With an empowerment-based approach and product innovation, this community service has succeeded in creating a sustainable and economically valuable waste management model